2017
DOI: 10.5812/zjrms.55105
|View full text |Cite
|
Sign up to set email alerts
|

Upright T Wave in Lead V1 as an Important Predictor of Significant Coronary Artery Disease in Patients with Chest Pain

Abstract: Background: Cardiovascular disease is a worldwide great burden on the health care syste early diagnosis and treatment of CAD can reduce the mortality and morbidity. We aimed to determine the association between upright T wave in lead V1 and coronary artery disease (CAD) in patients who presented with chest pain or positive non-invasive tests in emergency department. Methods: In this retrospective cross sectional design we reviewed the clinical and coronary angiography data of patients who had normal ECG. Prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The absence of normal precordial T-wave balance is one of the subtle signs of significant CAD (coronary artery stenosis >50%) in ECG. Studies have shown that the loss of precordial T-wave balance (T1 > T6), T-wave in V1 > 1.5 mm, and upright T-wave in V1 have been associated with significant CAD [12][13][14][15][16]. The reason for this is unclear and needs further research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of normal precordial T-wave balance is one of the subtle signs of significant CAD (coronary artery stenosis >50%) in ECG. Studies have shown that the loss of precordial T-wave balance (T1 > T6), T-wave in V1 > 1.5 mm, and upright T-wave in V1 have been associated with significant CAD [12][13][14][15][16]. The reason for this is unclear and needs further research.…”
Section: Discussionmentioning
confidence: 99%
“…Amirzadegan et al [15] Upright T-wave in V1 > 1.5 mm had OR = 2.38 (1.78 -3.12) for coronary artery stenosis of greater than 50%.…”
Section: Study Findingsmentioning
confidence: 99%
“…Less than 50% of people with Myocardial Infarction (MI) showed ST-wave changes in their initial ECG (13). T-wave changes were also shown to be associated with myocardial ischemia, and T-wave inversion was an important indicative of this disease (14). Furthermore, ECG abnormalities were associated with an increased risk of adverse cardiac events, including hypertrophic cardiomyopathy (15), fast heartbeat, prolonged PR interval and QT inversion, and abnormal changes in ECG axes (16).…”
Section: Introductionmentioning
confidence: 99%